2019
DOI: 10.14393/bj-v35n6a2019-42088
|View full text |Cite
|
Sign up to set email alerts
|

Control of Dalbulus maidis in maize crop with electrostatic spraying

Abstract: Among the pests that attack the maize, the maize leafhopper, which causes direct damages by sap-sucking and indirect ones, stands out as being a vector of pathogens and viruses, and can cause losses of up to 100% of the production. An alternative to improve the chemical control of this pest is the use of electrostatic spraying technology. However, there is no research support. This study aimed to evaluate the deposition of spray in the maize crop and the effectiveness in the chemical control of the maize leafh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The deposition observed by the electrostatic technique in the upper third of the maize plant surpassed the conventional application in almost 50 % of the tracer mass retained in the first application and almost 30 % in the second application (Table 4). These results are in agreement with the results reported by Marques et al (2019) for the same crop and position in the plant canopy, where the authors achieved an increase of 64 % in the tracer deposition with the use of the electrostatic technique. TABLE 4.…”
Section: Test 1 and 2 -Determination Of The Electrical Conductivity Osupporting
confidence: 92%
See 1 more Smart Citation
“…The deposition observed by the electrostatic technique in the upper third of the maize plant surpassed the conventional application in almost 50 % of the tracer mass retained in the first application and almost 30 % in the second application (Table 4). These results are in agreement with the results reported by Marques et al (2019) for the same crop and position in the plant canopy, where the authors achieved an increase of 64 % in the tracer deposition with the use of the electrostatic technique. TABLE 4.…”
Section: Test 1 and 2 -Determination Of The Electrical Conductivity Osupporting
confidence: 92%
“…Averages followed by similar letters in the column do not differ by Tukey' s test (p < 0.05). CV (%) = coefficient of variation Losses to the soil in the first and second applications showed that the electrostatic technique decreased the risk of environmental contamination and the waste of spray solution, as demonstrated by other studies (Marques et al, 2019;Zhou et al, 2012). The electrostatic sprayer can create a zone of electromagnetic interference; thus, when the droplets are sufficiently electrified, they tend to follow the trajectory of the electromagnetic field lines that are created due to the difference in the electric potential among the soil, vegetation, and electrified nozzle.…”
Section: Application Techniquementioning
confidence: 54%